Mysteries of Asia - Spry-Leverton, Peter; Spry-Leverton, Peter; Bell, Michael (Mysteries of Asia, 1999)
Documentary focusing on Angkor Wat, the extinct city in Cambodia. Examines the particular natural forces that encouraged the building of this vast Buddhist temple and how it relates to the history of Cambodia from ancient times through the rule of Pol Pot.